Calcium Oxide from Waste Shells as Potential Green Catalyst for Biodiesel Production - Nasir, Nurul Fitriah; M. M. Hazri (Research Progress in Mechanical and Manufacturing Engineering, 2020)
This paper concentrating on characterizing the effect of various calcination temperatures on calcium oxide (Ca-O) derived from waste shells as an alternative economic heterogeneous catalyst. The characterization of green-based heterogeneous catalysts, prepared from waste mussel shells, is investigated in this case study. The waste mussel shell catalyst was prepared for 4 hours at different high calcination temperatures of 900, 950, and 1000°C with continuous nitrogen gas supply at a 5°C per minute heating rate. Catalyst characterized by different methods: a study of X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX), and Fourier Transform Infrared Spectroscopy (FTIR). From the results, a trend of different temperatures for the calcium oxide catalyst derived from the mussel shells was analyzed to the optimal condition of the 950°C calcination process. The diffraction pattern of calcium oxide derived from decomposition at 950°C showed a trend close to calcium oxide developed by the Joint Committee on Powder Diffraction Standard (JCDPS), which between 32.3, 37.5, 54.0, 64.0, 67.2, 79.5 to 88.5 degrees in 2 theta ranges. A specific high-intensity FTIR spectrum occurs at a wavelength of 3642.84 cm-1 of decomposed calcium oxide of 950°C, similar to the particular vibration of Ca-O. Besides, a high surface area and pore diameter at 950°C calcination temperature was revealed in the morphology surface of the developed catalyst. The findings show that waste shells derived from mussels are feasible as a potential catalyst and expect to achieve a high yield conversion during the transesterification process.